To Consume or to Commune: Ruth 2.8-16 as a Resource for Pentecostal Economic Ethics - Padgett, Isaiah C. (Journal of pentecostal theology, 2025)
This article investigates how the text of Ruth 2.8-16 might serve to enrich the continued development of Pentecostal economic ethics. The sheer dominance of capitalistic modes of the consumption of resources and the commodification of persons have prompted an ongoing interest in developing Pentecostal theological responses to this issue. While the influence of Prosperity Pentecostalism continues as one such response, the growing desire to articulate alternative theological critiques requires attention to the breadth of Scripture that speaks to these concerns. As such, this article will attempt to demonstrate how the initial interaction between Ruth and Boaz in Ruth 2.8-16 reflects a counter to modern notions of consumption and commodification. It will be argued that this interaction demonstrates both God’s ultimate ownership of creation and the necessity of inviting the other into community, both of which have profound implications for Pentecostal economic ethics.